(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This study investigates the reproductive toxicity induced by ZnO nanoparticles and the protective role of Foeniculum vulgare (fennel)) through their potent against reproductive boxicity induced by zinc oxide (zno) nanoparticles in male rats. the significant protective role of Foeniculum vulgare and Pimpinella anisum. Herbalists really use fennel, whose scientific name is Foeniculum vulgare. Apiaceae is the family to which this plant belongs, which is often known as the Umbelliferae family. Organic formulations derived from Foeniculum vulgare offer a safer alternative to synthetic medications.